True Restriction in Diffusion-Weighted Imaging in a Mistreated Patient With Phenylketonuria. Issue 1 (January 2021) - Palaiodimou, Lina; Zompola, Christina; Lachanis, Stefanos; Mylona, Varvara; Theodorou, Aikaterini; Papagiannopoulou, Georgia; Kotsali-Peteinelli, Vasiliki; Foska, Aikaterini; Kasti, Arezina; Skouma, Anastasia; Tsivgoulis, Georgios
Abstract : Introduction: Phenylketonuria (PKU) is the most common inborn error of amino acid metabolism and causes neurological manifestations because of excessive accumulation of phenylalanine (PHE). It can also affect adult patients who discontinue their treatment, even if they had been under adequate metabolic control during childhood. For that reason, it is recommended that PKU treatment should be continued throughout life and target PHE levels for adult patients should range between 120 and 600 μmol/L. Case Report: The authors present an adult patient with PKU who discontinued treatment and developed cognitive dysfunction because of high blood levels of PHE. Brain magnetic resonance imaging (MRI) of the patient was characteristic for PKU, presenting periventricular and callosal white matter hyperintensities in T2 and fluid-attenuated inversion recovery sequences, which were additionally associated with true restriction in diffusion-weighted imaging sequence, a far less recognized PKU neuroimaging feature. Discussion: Cognitive dysfunction and psychiatric disorders can be present in adult patients with PKU who discontinue treatment and have poor PHE metabolic control. The presence of white matter hyperintensities in T2 and fluid-attenuated inversion recovery MRI-sequences is a well-described neuroimaging feature of PKU, but diffusion-weighted imaging sequence may also be reliable in detecting brain lesions in patients with PKU. PKU lesions should be considered in the differential diagnosis of true diffusion restriction in brain MRI of patients with PKU history or those who might have escaped newborn screening diagnosis but present neurocognitive dysfunction. Appropriate treatment for the management of PKU should be initiated for the reversal of the clinical and neuroimaging findings.